Effects of a humanized CD47 antibody and recombinant SIRPα proteins on triple negative breast carcinoma stem cells - Kaur, Sukhbir; Reginauld, Bianca; Razjooyan, Sam; Phi, Trung; Singh, Satya P.; Meyer, Thomas J.; Cam, Margaret C.; Roberts, David D. (Frontiers in Cell and Developmental Biology, 2024)
Signal regulatory protein-α (SIRPα, SHPS-1, CD172a) expressed on myeloid cells transmits inhibitory signals when it engages its counter-receptor CD47 on an adjacent cell. Elevated CD47 expression on some cancer cells thereby serves as an innate immune checkpoint that limits phagocytic clearance of tumor cells by macrophages and antigen presentation to T cells. Antibodies and recombinant SIRPα constructs that block the CD47-SIRPα interaction on macrophages exhibit anti-tumor activities in mouse models and are in ongoing clinical trials for treating several human cancers. Based on prior evidence that engaging SIRPα can also alter CD47 signaling in some nonmalignant cells, we compared direct effects of recombinant SIRPα-Fc and a humanized CD47 antibody that inhibits CD47-SIRPα interaction (CC-90002) on CD47 signaling in cancer stem cells derived from the MDA-MB-231 triple-negative breast carcinoma cell line. Treatment with SIRPα-Fc significantly increased the formation of mammospheres by breast cancer stem cells as compared to CC-90002 treatment or controls. Furthermore, SIRPα-Fc treatment upregulated mRNA and protein expression of ALDH1 and altered the expression of genes involved in epithelial/mesenchymal transition pathways that are associated with a poor prognosis and enhanced metastatic activity. This indicates that SIRPα-Fc has CD47-mediated agonist activities in breast cancer stem cells affecting proliferation and metastasis pathways that differ from those of CC-90002. This SIRPα-induced CD47 signaling in breast carcinoma cells may limit the efficacy of SIRPα decoy therapeutics intended to stimulate innate antitumor immune responses.